Attitudes Toward Death in Emerging Adulthood After the Emerging Infectious Disease COVID-19 - Dewi, Erviana Laksito; Rahayu, Maria Nugraheni Mardi (Psikoborneo: Jurnal Ilmiah Psikologi, 2026)
Following the outbreak of the emerging infectious disease COVID-19, there has been a shift in young adults' perspectives on death. This study aims to provide an overview of differences in attitudes toward death based on gender, religious perception, and experiences during the pandemic (as survivors, loss of loved ones, both, or neither). The method used was quantitative descriptive with the Death Attitude Profile—Revised (DAP-R) instrument and involved 225 participants through accidental sampling. The results show that the majority of Indonesian young adults have a high neutral acceptance (85.8%) and approach acceptance (64.9%) attitude, but some also show fear of death (40%) and death avoidance (41.8%). Women tend to have a higher fear of death and death avoidance attitude than men, while other attitudes are relatively balanced. Based on perceptions of religiosity, the religious group showed higher scores on neutral acceptance (87.1%) and approach acceptance (70.3%), although not always lower in fear or avoidance of death than the non-religious group. Meanwhile, based on pandemic experiences, all groups showed a predominance of fear of death, but individuals who were grieving and experienced both (“being a survivor and experiencing loss”) showed higher acceptance scores than other groups These findings enrich our understanding of the dynamics of attitudes toward death among young Indonesian adults post-crisis as reviewed by gender, religious perception, and experiences during the pandemic.Setelah merebaknya emerging infeksius disease COVID-19 terjadi pergeseran dalam cara pandang individu emerging adulthood terhadap kematian. Penelitian ini bertujuan untuk memberikan gambaran perbedaan sikap terhadap kematian berdasarkan jenis kelamin, persepsi religiusitas, dan pengalaman selama pandemi (sebagai penyintas, kehilangan orang terdekat, keduanya, atau tidak mengalami keduanya). Metode yang digunakan adalah deskriptif kuantitatif dengan instrumen Death Attitude Profile—Revised (DAP-R) dan melibatkan 225 partisipan melalui accidental sampling. Hasil menunjukkan bahwa mayoritas dewasa muda Indonesia memiliki sikap neutral acceptance (85,8%) dan approach acceptance (64,9%) yang tinggi, namun sebagian juga menunjukkan fear of death (40%) dan death avoidance (41,8%). Perempuan cenderung memiliki rasa takut terhadap kematian dan sikap menghindari kematian yang lebih tinggi daripada laki-laki, sementara sikap lainnya relatif seimbang. Berdasarkan persepsi religiusitas, kelompok religius menunjukkan skor lebih tinggi pada neutral acceptance (87,1%) dan approach acceptance (70,3%), meskipun tidak selalu lebih rendah dalam ketakutan atau penghindaran terhadap kematian dibanding kelompok non-religius. Sementara itu, berdasarkan pengalaman pandemi semua kelompok menunjukan dominasi fear of death, tetapi individu yang berduka,  dan mengalami keduanya  (menjadi penyintas dan mengalami kehilangan) menunjukkan skor acceptance lebih tinggi dibandingkan kelompok lain. Temuan ini memperkaya pemahaman dinamika sikap terhadap kematian pada dewasa muda Indonesia pasca-kriris yang ditinjau oleh jenis kelamin, persepsi agama, dan pengalaman selama pandemi.